The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jcla.21924
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Standard Chlamydia trachomatis Culture Method Is Improved After One Additional In Vitro Passage

Abstract: The results of this study support the use of a three-passage Chlamydia culture procedure to increase the detection sensitivity of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This sensitivity may be further reduced by culture overgrowth by commensal bacteria [47]. Recently, however, Shao et al demonstrated an increased culture sensitivity by performing additional in vitro passages compared to standard protocols and reported a culture sensitivity of 80% after three blind culture passages [48], but this will lengthen the time to diagnosis even more. Culture methods have mostly long turnaround times of at least 24 h and up to 3 days post infection without additional in vitro passages and with its labor intensive and demanding procedure, chlamydia culturing is not available in most routine laboratory settings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This sensitivity may be further reduced by culture overgrowth by commensal bacteria [47]. Recently, however, Shao et al demonstrated an increased culture sensitivity by performing additional in vitro passages compared to standard protocols and reported a culture sensitivity of 80% after three blind culture passages [48], but this will lengthen the time to diagnosis even more. Culture methods have mostly long turnaround times of at least 24 h and up to 3 days post infection without additional in vitro passages and with its labor intensive and demanding procedure, chlamydia culturing is not available in most routine laboratory settings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…It has been inferred that the accumulation of antibiotics in patients can limit CT growth during early passages. 34 In addition, some experts have reported that in vitro exposure to several β-lactam antibiotics causes the reticulate body of CT to convert to the aberrant reticulate body phenotype found in a persistent state. 25 Therefore, the administration of amoxicillin can cause CT to enter a persistent state.…”
Section: Discussionmentioning
confidence: 99%
“…A two-passage culture method was applied in all clinical swabs because we found that there were only a small amount of inclusions formed in the clinical swabs in the first passage; thus, the sensitivity of CT iodine staining could be increased with multiple passages. 34 The successfully cultured CT strains were stored in sucrose phosphate glutamate (218 mM sucrose, 3.76 mM KH 2 PO 4 , 7.1 mM K 2 HPO 4 , and 5 mM GlutaMAX-100—all purchased from the Solarbio Technological Co, Ltd. Beijing, China) storage medium at −80 °C for further use.…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, these approaches will break the transmission chain and prevent serious sequels. Regarding the detection methods, Chlamydia is not effectively detected by the conventional methods (using culture) because, despite the associated higher specificity, its sensitivity has a range from 3.9 to 80%, which is related to false negatives (~39%) [ 22 ]. Moreover, using cultures is expensive, requires approximately three to seven days, and is not technically simple.…”
Section: Introductionmentioning
confidence: 99%